New directions for preserving intangible cultural heritage through the use of mobile technologies - Papangelis, Konstantinos; Chamberlain, Alan; Hai-Ning, Liang (2016)
While many cultural heritage projects currently exist, few explore the full potential of mobile technologies as a mechanism to explore intangible heritage as a way to preserve culture. This paper outlines three distinct areas necessary for the design, development and application of mobile technologies within this domain. We represent these as: a) The documentation of traditions within their unique context, as articulated by the represented community—co-curated; b) The translation of traditions and their modes of expression into emerging technology-based designs; c) Co-design and ethnography as approaches to build meaningful mobile experiences.